George Sand, antisex feminist - Counter, A (Duke University Press, 2023)
George Sand's feminist novels of the 1830s often seem to have a “problem” with sex, or to view sex as a problem. In them, heterosexual sex often appears disempowering for women and therefore politically unpalatable; worse, heterosexual desire itself emerges as primordially marked by patriarchal constraints, predicated on the (self‐)objectification and subjection of women. This article offers a speculative reading of Sand's early fictions as anticipating similar “antisex” attitudes in later twentieth‐century feminism (the so‐called antipornography feminism of the 1980s), and uses close readings of moments in Indiana, Mauprat, and Lélia to reflect on the renewed urgency—in the wake of #MeToo—of the sort of ethical questions raised by such feminism during the “sex wars.” If Sand is not, ultimately, an antisex feminist, her novels are nevertheless thought‐provoking in their skepticism, or their pessimistic realism, about the possibility of a politically or ethically motivated reform of sex and desire.